For number 1, theat is not a right triangle as a squared plus b squared does not equal c squared
Answer:
c=8
Step-by-step explanation:
Simplifying
3c + -15 = 17 + -1c
Reorder the terms:
-15 + 3c = 17 + -1c
Solving
-15 + 3c = 17 + -1c
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add 'c' to each side of the equation.
-15 + 3c + c = 17 + -1c + c
Combine like terms: 3c + c = 4c
-15 + 4c = 17 + -1c + c
Combine like terms: -1c + c = 0
-15 + 4c = 17 + 0
-15 + 4c = 17
Add '15' to each side of the equation.
-15 + 15 + 4c = 17 + 15
Combine like terms: -15 + 15 = 0
0 + 4c = 17 + 15
4c = 17 + 15
Combine like terms: 17 + 15 = 32
4c = 32
Divide each side by '4'.
c = 8
Simplifying
c = 8
Answer:
-4
Step-by-step explanation:
1. Always start with the parenthesis. (26/13) = 2
2. Then multiply. 2*-7 = -14
3. After, you add 14 to your precious answer (-14) then subtract 4.
-14 + 14 = 0 - 4 = -4
Multiply both sides by 10.
2b=990
divide both sides by 2
b= 495
Answer:
1x + 4y = 4 ⇒ 6x + 24y = 24
6x - 8y = 0 ⇒ 6x - 8y = 0
32y = 24
32 32
y = 3/4
x + 4(3/4) = 4
x + 3 = 4
-3 -3
x = 1
(x, y) = (1, 3/4)
Step-by-step explanation:
up there :D